2020
DOI: 10.1038/s41467-020-18451-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil age on ecosystem structure and function across biomes

Abstract: The importance of soil age as an ecosystem driver across biomes remains largely unresolved. By combining a cross-biome global field survey, including data for 32 soil, plant, and microbial properties in 16 soil chronosequences, with a global meta-analysis, we show that soil age is a significant ecosystem driver, but only accounts for a relatively small proportion of the cross-biome variation in multiple ecosystem properties. Parent material, climate, vegetation and topography predict, collectively, 24 times mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Studies on soil chronosequences have shown that progressing soil age not only implies increasing SOC contents, but also changes in soil organic matter quality (Shi et al 2006;Egli et al 2010;Clark et al 2012;Chaudhuri et al 2015;Kumar et al 2018;Khedim et al 2020), which in turn dictates biogeochemical processes (Shi et al 2006;Banning et al 2008). Recently, Delgado-Baquerizo et al (2020) showed that soil age indeed drives local-scale ecosystem properties associated with biological activity, such as soil N:P and C:P ratios, microbial biomass, fungal:bacterial dominance or SOC stocks. Thus, microbial responses to FT events may be indirectly linked to soil age via temporal changes in soil biogeochemical characteristics (Yanai et al 2004;Allison et al 2005Allison et al , 2007bMoore et al 2010;Delgado-Baquerizo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on soil chronosequences have shown that progressing soil age not only implies increasing SOC contents, but also changes in soil organic matter quality (Shi et al 2006;Egli et al 2010;Clark et al 2012;Chaudhuri et al 2015;Kumar et al 2018;Khedim et al 2020), which in turn dictates biogeochemical processes (Shi et al 2006;Banning et al 2008). Recently, Delgado-Baquerizo et al (2020) showed that soil age indeed drives local-scale ecosystem properties associated with biological activity, such as soil N:P and C:P ratios, microbial biomass, fungal:bacterial dominance or SOC stocks. Thus, microbial responses to FT events may be indirectly linked to soil age via temporal changes in soil biogeochemical characteristics (Yanai et al 2004;Allison et al 2005Allison et al , 2007bMoore et al 2010;Delgado-Baquerizo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Delgado-Baquerizo et al (2020) showed that soil age indeed drives local-scale ecosystem properties associated with biological activity, such as soil N:P and C:P ratios, microbial biomass, fungal:bacterial dominance or SOC stocks. Thus, microbial responses to FT events may be indirectly linked to soil age via temporal changes in soil biogeochemical characteristics (Yanai et al 2004;Allison et al 2005Allison et al , 2007bMoore et al 2010;Delgado-Baquerizo et al 2020). In line with this, the climatic history of soils can lead to a functional reorganization of the soil microbial community towards more tolerant species (Bardgett and Caruso 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the same line, Delgado-Baquerizo et al . [37] studied sixteen chronosequences across the globe. This meta-analysis showed that parent material type, climate, vegetation and topography have an over-ruling impact on ecosystem structure, and functioning and soil age plays a minor role.…”
Section: Role Of Soil Biota In Soil Formation and Habitat Creationmentioning
confidence: 99%
“…To achieve this aim, we used data from a global field survey of 235 natural ecosystems from nine biomes across six continents. The sampling sites included a wide range of vegetation, climate and soil types, and covered c. 73% of the environmental conditions found on Earth (Delgado-Baquerizo et al, 2020). We expected to detect distinct patterns of lichenised soil fungal distribution, driven by various environmental parameters, across different biomes worldwide.…”
Section: Introductionmentioning
confidence: 99%